Graphene oxide quantum dots disrupt autophagic flux by inhibiting lysosome activity in GC-2 and TM4 cell lines. (30th December 2016) - Ji, Xiaoli; Xu, Bo; Yao, Mengmeng; Mao, Zhilei; Zhang, Yuqing; Xu, Guofeng; Tang, Qiusha; Wang, Xinru; Xia, Yankai
Graphical abstract: Abstract: Graphene oxide quantum dots (GOQDs) have broad application prospects in many areas including bioimaging, drug delivery, DNA cleavage system, sensors and photocatalyst. Recently, increasing concerns have been raised about their biocompatibility, but studies about the effects of GOQDs on male reproductive system are still lacking. In this work, we explored the effects and molecular mechanisms of GOQDs on GC-2 and TM4 cells. We found autophagosome accumulation in GC-2 and TM4 cells after GOQDs treatment. Both LC3-II/LC3-I ratio and p62 levels increased, and the chloroquine-induced accumulation of LC3-II didn't enhance in the presence of GOQDs, which indicated that GOQDs blocked autophagic flux. Further studies found that the fusion between autophagosome and lysosome was not inhibited by GOQDs, but the proteolytic capacity of lysosome was weakened and both the expression and activity of cathepsin B reduced. Taken together, these results suggested that GOQDs blocked autophagic flux by decreasing the amount and enzymatic activity of cathepsin B and inhibiting lysosome proteolytic capacity in GC-2 and TM4 cells, which might have a potential hazard to male reproduction.